Identification of best technique in germination of musa gracilis - Muhammad Izzuan Zabidi (2013)
Musa gracilis is one of the wild banana species that grown in the highland forests at altitudes above 100 meters above the sea level. Wild banana Musa gracilis species can be identified based on morphological characteristics shown by the plant. Key features of the plant such as the position of the basic stem, flower bud shape, external color petal flower bud and leaf shapes as a guide to distinguish this species with other species. The main uniqueness of Musa gracilis is their flower bud that narrow shape and well-positioned upward. Because of that, it makes this wild banana species suitable as crop tropical landscape feature. In this research, two different techniques were conducted, in vivo and in vitro. Two techniques were chosen is to identify the best techniques in propagation of Musa gracilis. This is because to done the comparison the rate of germination percentage M. gracilis between the both techniques. Therefore, the best technique to germinate Musa gracilis can be identified to carry out breeding for the future. From this study, the embryo culture technique is the best technique to germinate the Musa gracilis compared to seed culture and seed sowing.